2021
DOI: 10.1038/s41571-021-00565-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment landscape of triple-negative breast cancer — expanded options, evolving needs

Abstract: Tumour heterogeneity and a long-standing paucity of effective therapies other than chemotherapy have contributed to triple-negative breast cancer (TNBC) being the subtype with the least favourable outcomes. In the past few years, advances in omics technologies have shed light on the relevance of the TNBC microenvironment heterogeneity, unveiling a close dynamic relationship with cancer cell features. An improved understanding of tumour-immune system co-evolution supports the need to adopt a more comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
472
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 669 publications
(553 citation statements)
references
References 224 publications
1
472
0
3
Order By: Relevance
“…TNBC is also associated with poorer prognosis than other subtypes of breast cancer, mainly due to higher frequency of metastasis, higher relapse rates and limited treatment options, with no conventional receptor-targeting therapeutics available compared to other breast cancer subtypes. However, owing to recent advances in the understanding of the distinctive biology and molecular features of TNBC, the TNBC therapeutic landscape of targeted therapies has been expanded with PARP inhibitors, antibody–drug conjugates and immune checkpoint inhibitors [ 3 ]. Nevertheless, platinum(II) chemotherapeutics such as cisplatin and carboplatin still remain the reference treatment of TNBC, either in adjuvant or neoadjuvant settings, and as monotherapy or in combination with other drugs [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…TNBC is also associated with poorer prognosis than other subtypes of breast cancer, mainly due to higher frequency of metastasis, higher relapse rates and limited treatment options, with no conventional receptor-targeting therapeutics available compared to other breast cancer subtypes. However, owing to recent advances in the understanding of the distinctive biology and molecular features of TNBC, the TNBC therapeutic landscape of targeted therapies has been expanded with PARP inhibitors, antibody–drug conjugates and immune checkpoint inhibitors [ 3 ]. Nevertheless, platinum(II) chemotherapeutics such as cisplatin and carboplatin still remain the reference treatment of TNBC, either in adjuvant or neoadjuvant settings, and as monotherapy or in combination with other drugs [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…We showed that in BT-20 cell lines, there is a correlation between the total n-10 fatty acid level and EGFR expression. This result can also have an impact in anti-EGFR therapies and in cases of resistance to EGFR inhibitors, suggesting to deepen the behavior of membrane remodeling as synergies for cancer cell resistance [ 37 ]. Overexpression and activation of AKT and mTOR, as sub-pathways of EGFR, are directly linked to the development of breast cancer [ 38 ], and we demonstrated that n-10 fatty acids have an impact on these two signaling proteins, in connection with but also independently from EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, research has expanded the targetable vulnerabilities in TNBC (Figure 1 and discussed below). Clinical efforts targeting multiple pathways, including DNA damage response, Epithelial-mesenchymal transition, (Wingless/Int-1) Wnt Signaling, Phosphatidylinositol-4,5-Bisphosphate 3-Kinase Catalytic Subunit Alpha (PIK3CA), and Androgen signaling, are currently ongoing, some of which are discussed below [15]. The standard of treatment for TNBC is neoadjuvant chemotherapy, which yields better pathologic complete response (pCR) [16].…”
Section: Recent Therapeutic Options and Molecular Targets In Tnbcmentioning
confidence: 99%